2017
DOI: 10.5219/656
|View full text |Cite
|
Sign up to set email alerts
|

Production and characterization of pectinase enzyme from rhizopus oryzae

Abstract: The research was conducted with the production of pectinase enzyme by fungal fermentation using Rhizopus oryzae and characterization of produced enzyme with respect to pH, temperature, incubation time, and substrate specificity. Carbon source was optimized replacing sugar with different concentration of pectin (0.5, 0.75, and 1.0%) during submerged fermentation. The outcomes of the fermentation process showed that media containing carbon source of 1% pectin replaced dextrose at pH 6.0 incubating for 72 hours a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 17 publications
3
5
0
Order By: Relevance
“…Pectinase production was correlated with biomass production. The results were similar to Chowdhury et al (2017). They reported that the pectinase production capacity of R. oryzae was optimal after an incubation period of 72 hours (3 days) and that the highest enzyme yield was achieved at the end of the log phase.…”
Section: Effect Of Incubation Time Ph and Temperature On R Stolonifer...supporting
confidence: 85%
See 1 more Smart Citation
“…Pectinase production was correlated with biomass production. The results were similar to Chowdhury et al (2017). They reported that the pectinase production capacity of R. oryzae was optimal after an incubation period of 72 hours (3 days) and that the highest enzyme yield was achieved at the end of the log phase.…”
Section: Effect Of Incubation Time Ph and Temperature On R Stolonifer...supporting
confidence: 85%
“…Some commercial pectinases are produced from Rhizopus. Rhizopus pectinase producers include R. oryzae (Chowdhury et al, 2017), Rhizopus sp. (Jaworska et al, 2022) and R. microspores (Abd El-Rahim et al, 2020).…”
Section: Identification Of Pectinolytic Fungimentioning
confidence: 99%
“…This is due to the higher the concentration of molds or microbes used, the higher the pectin in the substrate which can be degraded by microbes optimally. Chowdhury et al (2017) stated that molds can grow optimally, faster and higher if they are at higher concentrations which are balanced with substrate requirements so as to produce high biomass. In addition, supporting factors such as temperature and pH also affect the amount of production produced.…”
Section: Enzyme Productionmentioning
confidence: 99%
“…The advantage of this microbe is that it can be used in both wet (submerged) and dry (solid state) fermentations for the production of various important industrial products. The advantages of using Penicillium chrysogenum mold microbes are that they can be grown in a variety of wet and dry media conditions, are easy to breed, and have high enzyme production yields (Chowdhury et al, 2017). The fungi is often used to produce enzymes in solid media because it has the advantage of being easy to grow in liquid or solid media (Mufarrikha et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The effect of incubation periods for pectinase production was determined by incubation fermentation medium at different incubation periods viz., 3, 5, 7, 9, 11 and 13days. After that, the enzyme assay was carried out by DNS assay method (Chowdhury, et al, 2017).…”
Section: Effect Of Incubation Periodsmentioning
confidence: 99%